Counseling and Guidance on the Use of Date Palm Extract to Increase Breast Milk Flow in Breastfeeding Mothers - Sri Putriani Sinaga; Elvi Era Liesmayani; Meria Turnip; Wilda Wahyuni Siregar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
Breast milk is a vital source of nutrition for an infant's growth, development, and immune system. However, not all breastfeeding mothers are able to produce breast milk optimally, necessitating efforts to facilitate smooth milk production. Date palm extract is a potential non-pharmacological alternative, as it contains various nutrients, vitamins, minerals, and bioactive compounds that may support lactation. In light of this, a community service initiative was conducted in Sekip Village (Sederhana Hamlet), Lubuk Pakam, involving health education and guidance on the benefits and use of date palm extract to improve breast milk flow. The activity aimed to enhance breastfeeding mothers' knowledge and awareness regarding the importance of nutrition during lactation and to encourage successful exclusive breastfeeding. The methods employed included education, guidance, and evaluation using pre- and post-tests to assess breast milk flow. Results showed that prior to the intervention, 17 respondents (68%) experienced poor breast milk flow, while only 8 (32%) had good flow. Following the education, guidance, and a five-day regimen of date palm extract, the number of respondents with good breast milk flow increased to 21 (84%), while those experiencing poor flow decreased to 4 (16%). Furthermore, participants demonstrated increased knowledge and enthusiasm throughout the activity. Thus, education and guidance on the use of date palm extract serve as an effective non-pharmacological, health-promoting strategy to support smooth breast milk production, successful exclusive breastfeeding, and the overall health of mothers and infants.